Testing for drug and alcohol аbuse at the workplace - Zoran Kavrakovski; Katerina Jugreva; Biljana Bauer - Petrovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2009)
Drug and alcohol abuse in the workplace represents a great risk to employee's health and safety. More than 50% of the employees worldwide are related to easily accessible drug abuse, while 70% of the employees are related to alcohol abuse in the workplace. Tests for detecting drug and alcohol abuse in the workplace should be part of a new regulation, compulsory for all employees in the Republic of Macedonia. Implementing this sort of testing program should at the same time be a step towards devising particular solutions that shall bring about greater safety in the working environment. A key element in the implementation is to devise and establish an adequate policy that shall determine the risk factors within a working establishment which shall clearly express its position regarding drug and alcohol abuse during working hours. Along with the risk factors, the policy may also include the program for testing both, employees and the ones who are about to be employed, for drug and alcohol abuse. In order to implement this sort of test, it must be in accordance with the Occupational Safety and Health Act (Official gazette of the Republic of Macedonia, No 92/07, 2007) and a legal framework has to be defined, that shall regulate and solve numerous aspects of this issue, in order to fully implement the program for drug free working environment pursuant to the Declaration and the decrees of the United Nations General Assembly in 1998.